Evolution process of the Yinduba paleolandslide-dammed lake in the upper Jinsha River, SE Tibetan Plateau - Xu, Hui; Chen, Jian; Chen, Ruichen; Cui, Zhijiu; Mi, Dongdong; Shi, Lulu (Frontiers in Earth Science, 2023)
Based on field investigation, optically stimulated luminescence (OSL) dating and sedimentary analyses, this research shows that the Yinduba paleolandslide-dammed lake (PDL) was formed by a catastrophic rock avalanche damming Jinsha River before 74 ka ago. According to the blocked ancient riverbed, the lake depth was determined about 110 m and the corresponding lake length was about 22 km when the lake level reached the peak. Geomorphologic features of lacustrine terraces at Yinduba and river terraces on the residual dam body and OSL dating results indicate that Yinduba PDL is a dammed lake with multi-stage outbursts. Following the peak, due to the multi-stage breaching of the dam body, the lake level experienced two major drops until the dam breached entirely after 36 ka. The large dam size, special sedimentary structure, and semi-arid climate contribute to the long life of Yinduba PDL, which existed for approximately 38,000 years from its formation to its extinction. This study supports the possibility of a large landslide-dammed lake having the life span of up to tens of millennia, and provides new evidence regarding the evolutionary history of a dammed lake.